(untitled) (Damascus University Journal of Historical Studies, 2024)
Merchants residing in the city of Damascus formed three categories: Ottoman merchants, Arab merchants And foreign merchants, It arose among them on the one hand, And between themselves and the people of Damascus and its villages on the other hand, These financial relationships are summarized in three aspects: The first aspect is financial relations in the field of borrowing and lending money, The second aspect is in trade operations: Money for goods, and the third aspect is financial partnership operations, And renting shops especially from foreign traders, And the question is asked: What is the impact of the movement of this money in the city and its surroundings? It is necessary for merchants residing in a particular city. They use their money to do leaving a trace, It turned out to be positive in ways, And other negative aspects, Their trade revived the city, It impoverished some economic segments there, Their efforts contributed to the impoverishment of some villagers, All of this was handled using commercial court documents only, Because it is the court that decided the affairs of merchants of all categories.